Implementation of Pandeglang Regency Regional Regulation Number 4 of 2008 on Environmental Cleanliness, Beauty, and Order at Teluk Labuan Beach: A Siyasah Dusturiyah Perspective - M.Fathurrohman; Asro Asro; Muhammad Amin (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study analyzes the implementation of Regional Regulation of Pandeglang Regency Number 4 of 2008 concerning Environmental Cleanliness, Beauty, and Order (K3) at Teluk Labuan Beach during 2024–2025. The research is motivated by pressing environmental conditions, as data from SIPSN 2024 records an annual waste generation of 191,868.84 tons in Pandeglang Regency, with only about 34 percent properly managed. In addition, the 2024 Waste Management Performance Index (IKPS) places the regency at a low score of 44.7, particularly due to minimal human resource capacity and budget allocation. Teluk Labuan Beach, previously labeled among the dirtiest beaches in Indonesia by the Pandawara Group in 2023, continues to face recurring waste accumulation despite repeated clean-up initiatives. This study applies a descriptive qualitative method through in-depth interviews with key stakeholders, including the Environmental Agency, sub-district authorities, village officials, and local communities, supported by documentation and field observations. The analysis employs theories of legal effectiveness, policy implementation, and the perspective of siyasah dusturiyah. The findings identify several major challenges, including limited operational resources, low public awareness, weak enforcement of sanctions, and the natural topography of the bay that facilitates waste buildup. From the perspective of siyasah dusturiyah, the regulation’s implementation has not fully embodied the principles of public welfare and justice, indicating the need for stronger institutional commitment and comprehensive policy reinforcement.